Effectiveness of increasing the angle of lateral wedge insole on spatiotemporal gait parameters in patients with medial knee osteoarthritis - Bijarchian, M. H.; Majlesi, M.; Azadian, E. (Journal of Advanced Sport Technology, 2020)
In previous studies, the effect of lateral wedge insole on gait variables in people with medial knee osteoarthritis has been studied. However, No study was found to examine the effect of insole slope. This study was sought to assess the effect of increasing the angle of lateral wedge insole on spatiotemporal gait parameters in patients with medial knee osteoarthritis.Ten individuals with medial knee osteoarthritis and 10 healthy subjects with similar age, height and mass were selected. The spatiotemporal gait parameters of subjects were calculated in four walking conditions (walking barefoot, walking while wearing shoes with 0°, 5°, 11° insoles). Repeated measures and t-test was used in case of intragroup comparison and MANOVA in case of intergroup comparison. The main effect of insole had a significant effect on walking speed (p = 0.000). Walking speed in wearing shoes with 0° and 5° insoles were significantly higher than other condition. The intragroup analysis showed that walking speed, Double Support time, percent of foot off, and stride and step length in walking barefoot were significantly less than walking while using insoles in both groups. The speed of walking, stride and step length in barefoot conditions showed a significant difference between the two groups (p < 0.05). These findings imply that the use of insole was a similar effect in affected and non- affected limb. To increase the efficiency of gait, according to the results, recommended using laterally wedged insoles in people with medial knee OA.